Penerapan Model Pembelajaran Kooperatif Learning Tipe Group Investigation Pada Mata Pelajaran Akidah Akhlak di MTS TI Candung - Ramadani Ramadani; Muhiddinur Kamal; Zulfani Sesmiarni; Wedra Aprison (Universitas 45 Surabaya, 2023)
This study investigates the differences in the application of the Group Investigation type cooperative learning model in the Aqidah Akhlak subject at MTs Ti Candung with the application of the existing model on a theoretical basis. The Group Investigation type cooperative learning model refers to student participation in planning, including selecting topics and investigation methods consisting of 2-6 students with diversity, as well as making group reports. This research aims to begin the development of the steps taken by Akidah Akhlak teachers in implementing the Group Investigation type Cooperative Learning Model in class VIII 2 at MTs TI Candung. Apart from that, this research also highlights the factors that support and hinder Aqidah Akhlak teachers in implementing this learning model. This research method uses a descriptive qualitative approach by collecting data through direct observation in class VIII 2, interviews with Aqidah Akhlak teachers and students, as well as analysis of documents such as lesson plans. The research results show that the development steps implemented by teachers are not fully in accordance with the theory explained by Sharan. For example, group division based on student absences is not always heterogeneous, and the selection of learning topics is generally made by the teacher rather than the students. In addition, this research identified supporting factors such as increasing student participation in learning, increasing cooperation between groups, and training in public speaking skills. However, inhibiting factors include the inability of some students to participate actively in group discussions and difficulty speaking in groups, which can hinder understanding of the material.